THE ROLE OF FOLK ORAL LITERATURE SAMPLES IN DEVELOPING COMMUNICATIVE COMPETENCE IN ENGLISH LANGUAGE LESSONS - Maxsumova Maftuna Zoirjonovna (International Journal of Literature and Language Studies, 2026)
This article provides a theoretical analysis of the role of folk oral literature samples in developing communicative competence among learners in English language lessons. The study examines the relationship between the structural components of communicative competence – linguistic, socio-cultural, discursive, and strategic – and the pedagogical potential of folk oral literature. The research draws on theoretical sources in linguodidactics, folklore studies, and communicative language teaching methodology. The findings indicate that the application of folklore genres such as folk tales, proverbs, riddles, and epics in English language lessons simultaneously promotes learners’ speech activity, intercultural communication skills, and national self-awareness.